Kuarter Kerajaan 217G-217L, Jalan Burmah, Pulau Pinang - Mohd. Hafizzudin Mohd. Zahir; Lo, Siaw Kin; Phang, Jeffery Siaw Foong; Rohaizad Hazil; Liew, Eugene Pek Wan (Skudai : Universiti Teknologi Malaysia, 1996)
Kajian Lukisan Terukur (Fakulti Alam Bina) - Universiti Teknologi Malaysia, 1996